Reflectivity enhancement in titanium by ultrafast XUV irradiation - Bencivenga, F. (Nature Publishing Group, 2014)
The study of highly photo-excited matter at solid state density is an emerging field of research, which is benefitting the development of free-electron-laser (FEL) technology. We report an extreme ultraviolet (XUV) reflectivity experiment from a titanium (Ti) sample irradiated with ultrafast seeded FEL pulses at variable incident photon fluence and frequency. Using a Drude formalism we relate the observed increase in reflectivity as a function of the excitation fluence to an increase in the plasma frequency, which allows us to estimate the free electron density in the excited sample. The extreme simplicity of the experimental setup makes the present approach potentially a valuable complementary tool to determine the average ionization state of the excited sample, information of primary relevance for understanding the physics of matter under extreme conditions.